2011
DOI: 10.1007/s10238-011-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of Endostar on the angiogenesis and growth of gastrointestinal stromal tumor xenograft

Abstract: To investigate whether Endostar can inhibit the angiogenesis and growth of gastrointestinal stromal tumor (GIST) xenografts in nude mice and the feasibility of antiangiogenesis as a treatment modality for GIST. Twenty Balb/c-nu/nu mice burdened with GIST were randomly divided into two groups. Endostar (2 mg/kg) was injected around the tumor once per day for 10 days in the experimental group and with normal saline (NS) (0.1 ml) in the control group. The tumor bulk was measured every 5 days until 5 days after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As a functional angiogenesis inhibitor, Endostar is at least twice as efficient as endostatin in animal tumor models 20) . It also reduces inoculated tumor growth in mice by substantially inhibiting angiogenesis 21) . In the recent pilot clinical trial, Endostar, combined with chemotherapy, was well tolerated in patients with metastatic colorectal and gastric cancers 22) .…”
Section: Introductionmentioning
confidence: 99%
“…As a functional angiogenesis inhibitor, Endostar is at least twice as efficient as endostatin in animal tumor models 20) . It also reduces inoculated tumor growth in mice by substantially inhibiting angiogenesis 21) . In the recent pilot clinical trial, Endostar, combined with chemotherapy, was well tolerated in patients with metastatic colorectal and gastric cancers 22) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other mechanisms can also contribute to the combination effect. For example, Endostar may very well contribute to the synergism via anti‐angiogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…To further increase the antitumour activity of Fv-LDP, we explored a new strategy for cancer therapy by combining Fv-LDP and Endostar, which was not related to the cytotoxicity of AE (the active moiety of LDM). Endostar is a known modified recombinant human endostatin and has been approved for clinical use in China [26]. Endostar can also At day 0, 1.5 9 10 6 murine hepatoma 22 cells ascites-passaged were directly transplanted subcutaneously into the right axilla of mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ES group, the majority of lesions subsided, but the fading time was slower than that of the control group. In the DVP graph for the regression of tumour lesions, the extinction process curve was not uniform, which indicated that the microvessel density within the lesions differed (15). In the RT and ES + RT groups, contrast enhancement as a slow in/slow out change was observed, indicating vascular damage and suppression following radiotherapy.…”
Section: Discussionmentioning
confidence: 99%